Coronal sealing ability of different sealers on teeth obturation and the effectiveness of two different obturation techniques - Saeed, Media A.; Toma, Intesar S.; Saeed, Dara H. (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objectives: The purpose of this study was to evaluate the effect of two sealers on coronal seal and the coronal sealing ability of two obturation techniques. Methods: Forty extracted single–rooted human teeth were instrumented with the step-back technique and were irrigated with 5.25% sodium hypochlorite (NaOCl). The smear layer was removed by washing with 10 ml of 17% ethylene diamine tetra-acetic acid (EDTA) and 10 ml of 5.25% (NaOCl). All instrumented root canals were randomly divided into two experimental groups; Group A: 20 roots epoxy resin sealer (AH26) was used, Group B: 20 roots Zinc oxide euginol (ZOE) sealer was used. Each group of main groups were subdivided randomly into two obturation groups; 1. 10 roots obturated by thermo plasticized technique (obtura II), 2. 10 roots obturated by cold lateral compaction technique. The root surfaces were then coated with nail polish except for the coronal, then dye penetration study was conducted and samples were examined under the stereomicroscope. Data had been collected from three independent examiners and statistically analyzed using student t-test. Results: There were significant differences between AH26 with ZOE in group obturated by obtura II and when obtura II technique compared with the cold lateral compaction technique in group of AH26 sealer. Conclusion: Epoxy resin sealer (AH26) and obtura II gave the best results in coronal sealing when compared with Zinc oxide euginol sealer and cold lateral compaction technique.